2020
DOI: 10.3389/fpls.2020.559365
|View full text |Cite
|
Sign up to set email alerts
|

Golden Gate Cloning-Compatible DNA Replicon/2A-Mediated Polycistronic Vectors for Plants

Abstract: The expression of multiple proteins and high-throughput vector assembly system are highly relevant in the field of plant genetic engineering and synthetic biology. Deployment of the self-cleaving 2A peptide that mediates polycistronic gene expression has been an effective strategy for multigene expression, as it minimizes issues in coordinated transgene regulation and trait staking in plants. However, efficient vector assembly systems optimized for 2A peptide-mediated polycistronic expression are currently una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Agrobacterium-mediated transient expression analysis was performed as described by Lee et al[31] Agrobacterium tumefaciens LBA4404 cells carrying different sensor constructs were adjusted to OD600 0.4 in resuspension solution (10 mM MgCl 2 , 10 mM MES-KOH (pH 5.6), 100 μM acetosyringone) and infiltrated into leaves of 4 to 5-week-old Nicotiana tabacum cv. Samsun.…”
Section: Methodsmentioning
confidence: 99%
“…Agrobacterium-mediated transient expression analysis was performed as described by Lee et al[31] Agrobacterium tumefaciens LBA4404 cells carrying different sensor constructs were adjusted to OD600 0.4 in resuspension solution (10 mM MgCl 2 , 10 mM MES-KOH (pH 5.6), 100 μM acetosyringone) and infiltrated into leaves of 4 to 5-week-old Nicotiana tabacum cv. Samsun.…”
Section: Methodsmentioning
confidence: 99%
“…Advances in the assembly of large DNA fragments, where the exact number and arrangement of transgenes are determined, as well as increase in the efficiency of DNA cloning methods, have contributed significantly to the acceleration of the process of constructing a multigene expression cassette construct [ 37 ]. Currently, scientists have at their disposal a large array of kits/systems for implementing the intended strategy of constructing an expression cassette for plant transformation [ 38 , 39 ].…”
Section: Molecular Tools For Therapeutic Protein Production In Crop P...mentioning
confidence: 99%
“…Currently, scientists have at their disposal a large array of kits/systems for implementing the intended strategy of constructing an expression cassette for plant transformation [ 38 , 39 ]. The most commonly used include Golden Gate and derived methods such as MoClo (for chloroplast engineering), Golden Braid, and Green Gate, which are based on the use of type II restriction enzymes [ 37 ]. However, the latter feature is not entirely desirable in the case of large multigene constructs, due to numerous recognition sites.…”
Section: Molecular Tools For Therapeutic Protein Production In Crop P...mentioning
confidence: 99%
“…Our ability to deal with these technical challenges has been significantly enhanced by a burst of novel gene cloning and genome editing technologies in recent years. The Golden Gate cloning method is of particular interest because it allows the stacking of multiple genes in a straightforward manner ( Lee et al, 2020 ). Using this method, Ermakova et al recently demonstrated that a C4 photosynthetic pathway can be installed in rice by simultaneously expressing five maize photosynthetic enzymes using a single construct ( Ermakova et al, 2021 ).…”
Section: Textmentioning
confidence: 99%
“…Progress in C3-to-C4 engineering has been slow, however, due to a lack of understanding of the mechanisms underlying C4 photosynthesis. This status has changed recently with a number of important findings in C4 research ( Furbank, 2017 ; Sedelnikova et al, 2018 ) and technical breakthroughs ( Zhang et al, 2019 ; Lee et al, 2020 ; Zhu et al, 2020 ). Several new model plant species have also been introduced, such as Setaria viridis (a C4 monocot; Brutnell et al, 2010 ), Cleome gynandra (a C4 dicot; Newell et al, 2010 ), and the grass Alloteropsis semialata ( Lundgren et al, 2016 ).…”
Section: Textmentioning
confidence: 99%